Students’ and Teachers’ Perception on the Use of Edmodo in Learning and Teaching English at SMAN 6 Kendari - Gafar, Desriyanti; Aderlaepe, Aderlaepe; Husain, Desy Liliani (Journal of Teaching of English, 2021)
The purpose of the study is to examine the students’ and teachers’ perception towards the use of Edmodo in learning and teaching English process at SMA N 6 Kendari. The subjects of the study are the students in class XII. IPA1. This study used descriptive design. The researcher gathered the data through the questionnaire and interview. The data of students’ perception were collected by using close-ended questionnaire. The closed- ended questionnaire was analyzed with descriptive statistic by using SPSS16.0 version. The results showed that majority of students are having a positive response toward Edmodo. The result shows that 77.10% student are having positive respond, 14.40% students state neutral and only 8.50% students state negative. While, the result of interview showed that Edmodo helps the teacher to put on teach, to interact with the students, to monitor students’ activities groups and conduct evaluation. The recommendation of the research consists of two; the first is to the teachers, the teachers should use Edmodo in learning teaching English process as a media tools in learning and teaching English because it can improve the students' knowledge, motivation. In addition, it can make easy for teacher and students in learning and teaching English. The last is to the next researchers, the next researchers are suggested to do similar research in different way such as; the next researcher should try to search the effect of using Edmodo in teaching English. It would see whether the use of Edmodo can give significant effect.